Global Environmental Health Impacts of Rare Earth Metals: Insights for Research and Policy Making in Africa - Habeebullah Jayeola Oladipo; Yusuf Amuda Tajudeen; Emmanuel O. Taiwo; Abdulbasit Opeyemi Muili; Rashidat Onyinoyi Yusuf; Sarat Ayomide Jimoh; Muhammad Kamaldeen Oladipo; Iyiola Olatunji Oladunjoye; Oluwaseyi Muyiwa Egbewande; Yusuff Inaolaji Sodiq; Abdulhakeem Funsho Ahmed; Mona Said El-Sherbini (Challenges, 2023)
The rise of globalization and industrialization has driven the demand for rare earth metals (REMs). These metals are widely used in various sectors of the global economy with various applications in medicine, renewable energy, electronics, agriculture, and the military. REMs are likely to remain an important part of our global future, and, as production increases, areas contaminated by REMs are expected to expand over the coming decades. Thus, triggering significant adverse environmental, animal, and human health impacts. Despite increased attention on REMs outside China in recent years, there are limited studies exploring REM production, deposits, and associated health impacts in the African context. Proper mine management, adequate safety protocols, sustainable processing methods, and waste handling systems have been identified and proposed globally; however, the nature and scale of implementing these management protocols on the African continent have been less clear. Therefore, planetary health-centered solutions are urgently needed to be undertaken by researchers, policy makers, and non-governmental actors in Africa and across the globe. This is with the overarching aim of ensuring eco-friendly alternatives and public health consciousness on REM exploitations and hazards for future generations to come.